The round wardrobe - Mohammad Faiz Azmi, Ahmad Nordin (2011)
Wardrobe was the place to keep clothes. Every wardrobe has various features and designs. Usually conventional wardrobe shape is rectangular. Most wardrobes are placed inside the bedroom and placed near the wall or wall vertex. Usually the clothes is placed in clothes compartment or hanged and this will caused difficulty to choose and pick clothes. To overcame this problem a new type of wardrobe is designed. This wardrobe is in round shape and it can be rotate in 360 degree to overcame the problem where the user need to spend more time to find, to choose, to pick and further to hanged back their clothes to its original place. This design also consider contact time while picking the clothes. Firstly, there have four concept of round wardrobe is designed. However, concept number four is selected after having true scoring and screening process later this concept is modelled in actual dimension in solid work. As a pilot modelling it have been scale 1:4 has been chosen to simplify the analysis process. This product later involved in various processes such as material selection, measuring, grinding, assembly and finishing. The advantage of this new product is, it comes in round shape, can be rotated and in the aspect of space, this product can be placed anywhere in clothing room. This wardrobe has achieved the objective successfully